COVID‐19 test result reporting for deceased donors: Emergent policies, logistical challenges, and future directions - Lentine, Krista L. (Clin Transplant, 2021)
The coronavirus disease 2019 (COVID‐19) pandemic poses unprecedented challenges to the transplant community, including organ procurement organizations (OPOs), transplant centers, regulatory agencies, and recipient candidates. Access to timely, accurate information on the status of deceased donor viral infection is essential in determining organ acceptance. The Organ Procurement and Transplantation Network expeditiously added fields to collect these data; however, use of the data collection fields was not uniform nationally. Standardized, field‐defined data capture and reporting are vital to ensure optimal organ utilization during this pandemic, and to prepare the community for subsequent challenges.